A new species of Catenes Distant from South America (Hemiptera, Heteroptera, Lygaeoidea, Rhyparochromidae) - Dellapé, Pablo Matías (2008)
Fil: Dellapé, Pablo Matías. División Entomología. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina